Histological outcome of atypical squamous cells cannot exclude high-grade squamous intraepithelial lesion (asc-h) papanicolaou smears diagnosed at Groote Schuur hospital - Wessels, Raisa (Department of Pathology, 2025)
Background - Cervical cancer imparts a huge burden on South African women and the healthcare system, making up 17.33% of all cancers in females. Cervical cytology screening, assessed under the Bethesda system, forms an integral part of this effort. Within this system, the Atypical Squamous Cells, cannot exclude High grade squamous intraepithelial lesion (ASC-H) category is said to carry a positive predictive value for High grade Squamous Intraepithelial neoplasia (HSIL) that lies between Atypical Squamous Cells of Uncertain Significance (ASC-US) and HSIL. Aim: The aim of this study was to assess the histological outcome of the ASC-H Papanicolaou smears diagnosed between January 2009 and December 2019 and to compare the yield of high grade histology with the literature. Methods: A computerized search of the Laboratory Information Systems (LIS) at Groote Schuur Hospital yielded 1694 ASC-H cases. Results: Of the 1694 cases identified, 699 cases had data on histology. Of the 699 cases with histology data, the majority of cases showed High Grade Squamous Intraepithelial Lesion (HSIL) on histology (n=271, 38.8%). There were 225 (32.1%) cases of Low grade Squamous Intraepithelial Lesion (LSIL), 75 (10.7%) showed normal histology, 40 (5.7%) cases showed cervicitis, 26 (3.7%) cases showed squamous cell carcinoma, 25 (3.6%) cases were suboptimal for assessment, 21(3.1%) cases showed squamous metaplasia and 16(2.3%) cases reflected diagnoses falling into an “other” category (which includes entities such as benign polyps and glandular lesions). Conclusion: With the larger proportion of cases showing HSIL, the intention of the ASC-H category to identify likely high risk cervical changes and expedite follow-up colposcopy, biopsy and management has been proven.